The usage of question and answer as an educational method: A Qur’anic outlook - Mamat , Arifin (2013)
Method of teaching is one of the most important pillars in the educational process. It can be defined as a series of guided activities, which are carried out by teachers to promote effective teaching and learning. Due to the importance of the method of teaching and its high position in the teaching and learning process, scholars throughout history have paid great attention to upgrading the position of the way to teach students. Fortunately, Muslims can find various methods of teaching in the Qur’an. One of the most popular methods used in the Qur’an is question and answer. Scholars are in views that skilful questioning performs a number of important functions. Therefore the Qur’an employed that method as a way to convey the message and ideas to people so that they may grasp them and act accordingly.